2019
DOI: 10.1680/jmapl.18.00033
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-compliance with structural building code standards in Nigeria

Abstract: Ahead of Print articles will move to that issue's Table of Contents. When the article is published in a journal issue, the full reference should be cited in addition to the DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was revealed that regulatory enforcement for flood disaster is very low at 62% responses. This is in tandem with Agapiou and Yakubu (2019) submission that lack of training and development causes noncompliance with standards and regulations in Nigeria construction industry. This is manifested in the case measurement for the distance of buildings from the river bank.…”
Section: Discussion Of Findingsmentioning
confidence: 89%
“…It was revealed that regulatory enforcement for flood disaster is very low at 62% responses. This is in tandem with Agapiou and Yakubu (2019) submission that lack of training and development causes noncompliance with standards and regulations in Nigeria construction industry. This is manifested in the case measurement for the distance of buildings from the river bank.…”
Section: Discussion Of Findingsmentioning
confidence: 89%